A new source of proteins, single cell proteins - ΕΥΣΤΑΘΙΟΥ Λ.; ΠΙΤΣΙΝΙΔΗΣ Γ.; ΠΑΠΑΔΟΠΟΥΛΟΣ Ε.; ΜΕΛΙΣΣΑΡΗΣ Χ. (Journal of the Hellenic Veterinary Medical Society, 2019)
Single cell proteins (S.C.P.) are produced by continuous Fermentation of single-cell microorganisms (i.e. bacteria, fungi, yeast) in starch, cellulose, carbohydrate and other substrates. Of the various substrates now in use, mollases, beet pubi and citrus pulp are of particular interest in our country. Recently, in our Research facilities we received a quantity of TOPRINA, a product of nparafTin fermentation which was subject to extensive dheminal analysis in terms of quality and nutrient value. Concurrently, the product was incorporated into specially computed poultry and swine ratios, in an attempt to study its effect on the growth performance of the above species and any possible toxic side effects. Growth performance of animals fed on TOPRINA was similar to that of the controls; toxic effects were not observed. Long term studies on toxicity, tissue residues and the consequences on the health and growth of our experimental animals were not carried out